Evaluating Children's Interaction with Touchscreens From 0 to 8 Years Old. (September 2018) - Soliman, Sommayah; Nathan-Roberts, Dan
Children start using mobile devices at a very young age. In this paper, we review the research done to evaluate children's capabilities and limitations when interacting with multi-touch screens. The different factors affecting children's touch gestures performance are evaluated. It was found that children are able to perform several complex touch gestures that are not currently used in applications targeting their age. The current research showed that children's usage of different multi-touch gestures is affected by their age and screen size. Design guidelines are recommended to improve young children's usability of multi-touch devices.